Enterprises Resource Planning for the DAM Information System in Indonesia - Bambang Handoko (Universitas Mercu Buana, 2021)
This research was conducted at the Ministry of Public Works and Public Housing, Director General of Water Resources, with a focus on research on the quality of dam data in Indonesia. The problem that occurs is that there is still a delay in data transmission by dam officials which causes the quality of realtime data to decline. This shows that there is a need for comprehensive research into the facts that occur in the field. The purpose of this research is to explore the perception that Indonesia is able to create and operate an ERP system with wide and large data coverage. The study uses the Value Stream Mapping method with a Descrete Event Simulation (DES) simulation to model a system that evolves with time. This study wants to know the future design (future state), namely developing an ERP (Entreprise Resource Planning) system based on IT technology (Information Technology) in improving the quality of integrated and realtime dam data. The results of this application are expected to have an increase in time efficiency above 95% which shows the overall time of the dam data delivery process (5 working days).